Деятельность наркомпроса Крымской АССР в 20-30 е годы - Абибуллаева, Д.И. (Культура народов Причерноморья, 2014)
В статье рассматривается политическая жизнь и деятельность наркомов просвещения
КАССР в годы сталинского тоталитарного режима. У статі розглядається політичне життя і діяльність наркомів освіти КАРСР в роки
сталінського тоталітарного режиму. The article focuses on the political and social changes in the Crimea, caused by the revolution of
1917, and the status of National Education of the Crimean Tatars. After the end of the Civil War and the
establishment of Soviet power in the peninsula, the new government established the People's Commissariat of
Education (Commissariat), which in the 20-30-is was, led by the People's Commissars (Ministers) from among
the Crimean Tatar intelligentsia. The article describes the life and work of the People's Commissars of
Education in the Crimea, in the conditions of the devastated economy, famine, political terror, and the complete
collapse of public education, particularly school education of the Crimean Tatars.
After the occupation of Crimea by the Soviet troops in 1920 IK Firdevs was invited as the chairman of Public
Education, and he began to implement the order of Krymrevkoma of 30 November 1920 "On the Restructuring
of the educational institutions," according to which all educational institutions in the Crimea were declared
Soviet and passed under the jurisdiction of the Soviet Socialist Republic. After IK Firdevs the post of Commissar
of Education was held by Khamzin K., M. Garyutin, Mukhitdinov, R. Nogaev U. Balich, M. Nedim, R.
Alexandrovich A., Asanov, B. Chagar. They were talented young people, full of optimism and confidence in the
bright future of their people. Their work was aimed primarily at improving education, culture and the material
level of the population of Crimea. Unfortunately all Commissars of Education have been victims of mass
political repressions. Their work is worth of deep research.